Potential roles of the CCL17‐CCR4 axis in immunopathogenesis of oral lichen planus. (2nd August 2019) - Shan, Jing; Shen, Chen; Fang, Jiaxiang; Li, Shan; Fan, Yuan
Abstract: Background: Oral lichen planus (OLP) is a T cell–mediated chronic inflammatory disease. C‐C chemokine receptor type 4 (CCR4) and its cognate C‐C motif chemokine ligand 17 (CCL17) play a key role in T‐cell activation and trafficking, but their implication in OLP pathogenesis has not been explored. Our study was designed to analyze the expression and function of the CCL17‐CCR4 axis in OLP. Methods: The mRNA expression levels of CCL17 and CCR4 in the circulating T cells of OLP subjects were examined by quantitative real‐time PCR. The protein levels of CCL17 and CCR4 in the peripheral blood of OLP subjects were detected by enzyme‐linked immunosorbent assay (ELISA) and Simple Western assay, respectively. The functional relevance of increased expression of CCL17 and CCR4 in OLP was demonstrated in proliferation, apoptosis, and migration assays. Results: The mRNA and protein expression levels of CCL17 and CCR4 in the peripheral blood of patients with OLP were significantly upregulated compared with those of controls. CCL17 induced the migration of OLP T cells. In addition, blocking CCR4 with a small molecule CCR4 antagonist not only inhibited the proliferation and migration of OLP T cells but also promoted the apoptosis of OLP T cells. Conclusion: Our findings indicate that the CCL17‐CCR4 axis might be responsible for the inflammatory infiltration of T cells in OLP.